Politics and decadence in Asimov’s Foundation Trilogy: Toynbee, Spengler and Polybius (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
Several scholars have analyzed the influence of Toynbee and Spengler, in the well-known saga of the Foundation, written by Isaac Asimov and considered one of the most important of science fiction. However, although there exists a transtextual dialogue with Spengler's and Toynbee’s works, our hypothesis is that the main hypertextual relationship must be searched in the work of the Greek historian Polybius, Histories. Comparing the anacyclosis described by Polybius with the political evolution that Asimov narrates in his novels, we can see that similarities not only reach different systems of government, but even the very same sequence in which they happen. The result is a work that allows an interesting palimpsestic reading, significantly enriching the experience of those readers possessing humanistic knowledge.
Keywords: Isaac Asimov; Foundation; Anacyclosis; Polybius